Education curricula should support the development of environmentally literate nurses - Mills, Anne (Evidence-based nursing, 2022)
Context Changes in the climate system as a direct consequence of human activities cause severe weather conditions, which adversely impact on human health.2 Nurses are the largest healthcare profession in the world and have the potential to significantly address the effects of climate change, in multiple ways, including reducing the world’s healthcare footprint, currently ‘4.4% of global net emissions’3. First-year nursing students were invited to complete the Sustainability Attitudes in Nursing Survey (SANS_2), which used a Likert- type scale. Within healthcare settings nurses can influence the procurement and efficient use of sustainable resources, including healthcare transportation systems, use climate friendly methods of waste disposal, and source locally grown fruit and vegetables.4 While also developing plans to manage climate change emergencies, caused by severe weather conditions.5 The multiple nursing everyday interactions with patients, provide opportunities to share climate change information to moderate effects.